BABUR THE FOUNDER OF MUGHAL EMPIRE IN INDIA - Ishfaq Ahmad Mir (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
The fourteenth century of the Christian period was a time of significant transition. The social and political environment was undergoing changes. Strong, centralized empires were erected in the east, while the middle classes in the west started to seek and obtain a part of government. Islamic control thrived during this period, bringing people from all over the globe together via trade and business. There were such powerful and centralized Islamic empires as the Mongols, Ottomans, Safavids, and Mughals. The Mughal Empire was made up of the conflicted, cooperative, and inventive relationships between the imperial dynasty and individuals from a wide range of cultural backgrounds in the numerous Indian territories that it was in charge of at the time. Three centuries' worth of rule might be attributed to the Empire. The Empire reached its zenith as the most powerful and prosperous state in human history